Development of Math Fun: An Android-Based learning Media Assisted by iSpring for Elementary Mathematics - Rodiah Faturohmah; Inne Marthyane Pratiwi; Yayan Carlian; Dadan F. Ramdhan; Hilman Mangkuwibawa (Al Ibtida: Jurnal Pendidikan Guru MI, 2025)
AbstractThe limited availability of mathematics learning media and the growing tendency of students to prefer smartphones over textbooks, presents challenges to the elementary learning process. Furthermore, advances in digital technology also offer opportunities to develop more engaging and interactive instructional media. Therefore, this research sought to design and evaluate a learning application, Math Fun, focused on the topic of two-dimensional (2-D) shapes for fourth-grade elementary students, as well as to assess its feasibility and user responses. The research employed a Research and Development (R&D) approach following the ADDIE instructional design model. Data were collected through observation, interviews, validation questionnaires, user response questionnaires, and a post-learning test. Validation results demonstrated a high level of feasibility, with scores of 89.58% from the material expert, 91.67% from the media expert, and 90% from the IT expert, each categorized as feasible. A limited trial involving 22 fourth-grade students from an elementary school in Garut Regency, West Java yielded a student response rate of 91.43% (excellent) and an average post-test score of 77.14, indicating that the learning objectives were successfully achieved. The findings confirm that Math Fun is a feasible and effective Android-based interactive learning medium for teaching 2-D shapes to fourth-grade elementary students.Keywords: android, mathematics learning media, math fun. AbstrakKeterbatasan ketersediaan media pembelajaran matematika dan meningkatnya kecenderungan siswa yang lebih memilih smartphone daripada buku teks, menghadirkan tantangan bagi proses pembelajaran di sekolah dasar. Di samping itu, kemajuan teknologi digital juga menawarkan peluang untuk mengembangkan media pembelajaran yang lebih menarik dan interaktif. Oleh karena itu, penelitian ini berupaya merancang dan mengevaluasi aplikasi pembelajaran, Math Fun, yang berfokus pada topik bentuk dua dimensi (2-D) untuk siswa sekolah dasar kelas empat, serta menilai kelayakannya dan respons pengguna. Penelitian ini menggunakan pendekatan Penelitian dan Pengembangan (R&D) mengikuti model desain instruksional ADDIE. Data dikumpulkan melalui observasi, wawancara, kuesioner validasi, kuesioner respons pengguna, dan tes pasca-pembelajaran. Hasil validasi menunjukkan tingkat kelayakan yang tinggi, dengan skor 89,58% dari ahli materi, 91,67% dari ahli media, dan 90% dari ahli TI, yang masing-masing dikategorikan layak. Uji coba terbatas yang melibatkan 22 siswa kelas empat SD di Kabupaten Garut, Jawa Barat menghasilkan tingkat respons siswa sebesar 91,43% (sangat baik) dan skor rata-rata postes sebesar 77,14, yang menunjukkan bahwa tujuan pembelajaran telah tercapai. Temuan ini menegaskan bahwa Math Fun merupakan media pembelajaran interaktif berbasis Android yang layak dan efektif untuk mengajarkan bangun ruang dua dimensi kepada siswa SD kelas empat.Kata kunci: android, media pembelajaran matematika, math fun.